PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI SEKOLAH DASAR PADA ERA GLOBAL - Mujinem, Mujinem (Fakultas Ilmu Pendidikan UNY, 2009)
Social studies are in general constructed in a systematic, comprehensive, and integrated manner in learning process toward maturity and success in society life. They are taught in order to learners achieve a wider confound comprehension in other related studies. For the purpose, professional teacher.','are required in the learning process, although they are not the only sources of knowledge. Globalization is characterized by the development of both information and communication technologies with the serious impact of making the world as the seemingly borderless area. Diverse foreign cultures can easily come through the borders of country with various impacts, both positive and negative. Teachers in the social studies are required to do something, so that negative impact from the outsiders can be minimized through the learning they do. In this case, the teachers of social studies should be professional in personality with a capacity of building the self of learners, particularly in intellectual capacity, and bring the learners to be citizen of the Republic of Indonesia under the nation's ideology. There fore, a professional teacher of social studies should master a much wider knowledge, specially related learning materials to be conveyed to the learners in the learning process. With understanding that the social studies are the kinds of memorizing based subjects and the materials are many so boring, in the global era the teachers have a special challenge, how do make the subject more pleasant one. A way that should be taken by the teacher is to build a commitment of strongly making the learners much more intelligent. With the commitment, teachers of the social studies can do as . follows: J) continuously improving knowledge through more sophisticated media, 2) seeking 10 master the sophisticated technology (computer), and 3) willing to use learning methods in accordance with the goals. Keywords: Learning, Social studies